Effect of Social Media Marketing on Customer Engagement and its Impact on Brand Loyalty in Caring Colours Cosmetics, Martha Tilaar - Muchardie, Brian Garda; Yudiana, Nabila Hanindya; Gunawan, Annetta (Bina Nusantara University, 2016)
The purpose of this research was to determine the influence of social media marketing against customer engagement and its impact on brand loyalty. Methods applied is a quantitative method by distributing questionnaire to 100 customers. Data analysis was applied path analysis. The results of this study shows that social media marketing has a positive and significant impact on customer engagement, on brand loyalty, and on customer engagement, and its impact on brand loyalty where customer engagement has a greater influence on brand loyalty than social media marketing.